Semantics, tense, and time : an essay in the metaphysics of natural language - Ludlow, Peter, 1957- (Cambridge, Mass. : MIT Press, 1999)
Annotation According to Peter Ludlow, there is a very close relation between the structure of natural language and that of reality, and one can gain insights into long-standing metaphysical questions by studying the semantics of natural language. In this book Ludlow uses the metaphysics of time as a case study and focuses on the dispute between A-theorists and B-theorists about the nature of time. According to B-theorists, there is no genuine change, but a permanent sequence of events ordered by an earlier-than/later-than relation. According to the version of the A-theory adopted by Ludlow (a position sometimes called presentism), there are not past or future events or times; what makes something past or future is how the world stands right now.
Preface -- Acknowledgements -- Introduction -- 1. The Nature of Language -- 2. The Form of the Semantic Theory -- 3. Attitudes and Indexicals -- 4. Drawing Metaphysical Consequences from a T-Theory -- 5. The B-Theory Semantics -- 6. Problems with the B-Theory Semantics -- 7. The A-Theory Semantics -- 8. Temporal Anaphora without B-Series Resources -- 9. Broadening the Investigation -- 10. Consequences -- Appendix P1 Is I-Language the Language of Thought? -- Appendix P2 Language/World Isomorphism?1 -- Appendix T1 A Basic Quantificational Fragment -- Appendix T2 A Quantificational Fragment with Events -- Appendix T3 A Fragment with ILFs for Propositional Attitudes -- Appendix T4 A B-Theory Technical Fragment -- Appendix T5 A Basic A-Theory Fragment -- Notes -- Bibliography -- Index.
"A Bradford book."
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Semantics; Language and languages -- Philosophy; Time; Metaphysics; Grammar, Comparative and general -- Tense; First philosophy; Semantics; Time; Metaphysics; Sémantique.; Langage et langues -- Philosophie; Temps; Métaphysique.; Temps (Linguistique); semantics; time; metaphysics; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Semantics; First philosophy; Grammar, Comparative and general -- Tense; Language and languages -- Philosophy; Metaphysics; Semantics; Time; Tijd; Semantiek; Metafysica